Pemberdayaan Masyarakat Padurenan Berbasis Experiential Literacy Learning untuk Mewujudkan Desa Bordir Berdaya - Agustino, Galeh Febrian; Raihan Aqila, Muhammad; Putri, Qorri 'Aina; Purwaningrum, Jayanti Putri (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
The Student Organization Capacity Strengthening Program (PPK Ormawa) by HIMATIKA Universitas Muria Kudus focuses on empowering the community of Padurenan Village, Gebog District, Kudus Regency, through an Experiential Literacy Learning approach to create a Smart Village based on the creative embroidery industry. This program stems from Padurenan’s great potential as a embroidery center, which faces challenges such as low youth interest, limited technical skills, and weak marketing strategies. Through the establishment of the Embroidery Literacy Corner, activities include program socialization, modern embroidery training, digital technology application, e-commerce and digital showcase workshops, basic financial management, and public speaking training. The results show significant improvements in participants’ knowledge, digital literacy, and entrepreneurial skills. Moreover, collaboration between experienced artisans and the younger generation has led to innovative embroidery products rooted in local wisdom and possessing high economic value. The program also encourages the formation of joint business groups and digital marketing networks, expanding market access. Overall, this initiative not only strengthens the competitiveness of Padurenan’s embroidery industry but also serves as a model of a sustainable Smart Village that integrates literacy, technology, culture, and the creative economy.